Vapor-liquid equilibrium data for binary mixtures of acetic acid plus anisole, acetone plus anisole, and isopropanol plus anisole at pressure 96.15 kPa - Mali, Nilesh A.; Mali, Pawan K.; Patil, Asmita P.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2017)
In this work, the vapor-liquid equilibrium (VLE) data have been generated at the local atmospheric pressure of 96.15 kPa for the binary systems acetic acid + anisole, acetone + anisole, and isopropanol + anisole. A circulation type apparatus was designed and developed with few modifications in one of the stills proposed in the literature. For the validation of the new apparatus, VLE data were generated for the known system of N,N-DMF + aniline and compared with the literature data. The VLE data, generated in Txy form for all pairs, were found to be consistent through the point-to-point consistency test. Activity coefficient models, Wilson, NRTL, and UNIQUAC, were fitted to these data using an objective function of minimizing the sum of deviation between experimental and calculated total pressures to estimate the binary interaction parameters. The model predictions with estimated parameters were compared with the experimental data and found appropriate.

Vapor-liquid equilibrium data for binary mixtures of dimethyl carbonate with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate at 93.13 kPa - Mali, Nilesh A.; Yadav, Satyajeet S.; Ghuge, Pravin D.; Joshi, Sunil. S. (Journal of Chemical and Engineering Data, 2017)
Isobaric vapor-liquid equilibrium (VLE) data was measured at the local atmospheric pressure of 93.13 kPa for the binary systems of dimethyl carbonate (DMC) with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate using a dynamic recirculation still. VLE data was generated in the form of T-x,y and was checked for thermodynamic consistency using the Herington area test, Van Ness test, and mean absolute deviation between experimental and calculated total pressure and vapor phase composition. Data for all pairs meet the criteria for thermodynamic consistency and were found suitable for process modeling. Binary interaction parameters for the Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models were determined using the objective function of minimizing the deviation between the experimental and the calculated vapor phase composition and total pressure. For all binary systems, Wilson, NRTL, and UNIQUAC models gave good predictions. Azeotropic behavior was observed for the isopropyl acetate-DMC pair at 357.8 K and 0.6 mole fraction of isopropyl acetate.